2023
DOI: 10.1111/dom.15017
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide changes postprandial responses of gut hormones involved in the regulation of gallbladder motility

Abstract: Aim Liraglutide treatment is associated with gallbladder‐related disorders and has been shown to delay postprandial gallbladder refilling. The gut hormones cholecystokinin (CCK), fibroblast growth factor 19 (FGF19) and glucagon‐like peptide 2 (GLP‐2), are known to regulate gallbladder motility and may be implicated in gallbladder‐related disorders associated with liraglutide treatment. Materials and Methods In a double‐blind, 12‐week trial, 52 participants [50% male, age 47.6 ± 10.0 years, body mass index 32.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Importantly, the related glucagon-like peptide-1 receptor agonists have recently been utilized for the treatment of nonalcoholic steatohepatitis, 22 although these therapies likely act via divergent pathways. 23 The main study strength is the analysis of detailed clinical trial data from a heterogeneous population. The main study limitation was a small sample size, which precludes subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the related glucagon-like peptide-1 receptor agonists have recently been utilized for the treatment of nonalcoholic steatohepatitis, 22 although these therapies likely act via divergent pathways. 23 The main study strength is the analysis of detailed clinical trial data from a heterogeneous population. The main study limitation was a small sample size, which precludes subgroup analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in liver chemistries were independent of reductions in PN/IV or changes in BMI. Importantly, the related glucagon‐like peptide‐1 receptor agonists have recently been utilized for the treatment of nonalcoholic steatohepatitis, 22 although these therapies likely act via divergent pathways 23 …”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies demonstrated that the postprandial FGF19 and GLP-2 concentrations were decreased and postprandial cholecystokinin was increased with GLP-1 analog use, which may result in delayed postprandial gallbladder refilling. 18 Cholangiocytes are susceptible to GLP-1 and respond with increased proliferation and functional activity, which may increase the risk of duct obstruction. 19,20 These findings all provided strong evidence for the association between GLP-1 RA treatment and gallbladder and biliary disease adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the weight loss effect of GLP‐1 analogs, independent mechanisms with the use of GLP‐1 analogs may also contribute to the increased risk of gallbladder and biliary disease. Experimental studies demonstrated that the postprandial FGF19 and GLP‐2 concentrations were decreased and postprandial cholecystokinin was increased with GLP‐1 analog use, which may result in delayed postprandial gallbladder refilling 18 . Cholangiocytes are susceptible to GLP‐1 and respond with increased proliferation and functional activity, which may increase the risk of duct obstruction 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The body regulates the biliary system through humoral hormones and other cytokines, including cholecystokinin (CCK), which stimulates gallbladder contraction and bile secretion, as well as GLP-2 and FGF19, which promote gallbladder relaxation ( Choi et al, 2006 ; Yusta et al, 2017 ; Metry et al, 2023 ). The secretion of these hormones and signaling molecules is closely linked to bile acids in the gut ( Hansen et al, 2020 ; Miedzybrodzka et al, 2021 ; Nerild et al, 2023 ). The diastole of the gallbladder ensures the normal excretion of bile salts, cholesterol and phospholipids from the liver cells in order to reduce the amount of cholesterol in the serum and tissues of the body; while the regular contraction of the gallbladder ensures the power of the bile flow in the biliary system and reduces the time of bile retention, thus decreasing the probability of gallstones occurrence.…”
Section: Mechanisms Of Gallstone Formationmentioning
confidence: 99%